Strategi Menumbuhkan Cinta Ilahi pada Peserta Didik: Telaah Tematik Hadis Qudsi tentang Pedagogi Spiritual Islam - Sintaria Marsela; Althaf Javid H. Aziz; Muhammad Akmansyah (Al-Kindi, 2025)
Contemporary spiritual education is often trapped in formal ritualism without touching the essence of transcendence, resulting in profound spiritual emptiness among learners. This journal aims to analyze the urgency of Divine Love (Maḥabbatullāh) as the foundation of spiritualism and to identify pedagogical stages for cultivating it, sourced from thematic study of Hadith Qudsi (especially Hadith 9 regarding the closeness of servants). This research employs a qualitative method through thematic study (al-dirāsah al-mawḍū'iyyah) of Hadith Qudsi to identify patterns of Divine-human interaction. The research findings identify three pedagogical stages of Divine Love: Profession of Faith (Iqrār), Consistency of Faith (Istiqāmah), and Social-Spiritual Connectivity (Wasilah). These stages demonstrate that Maḥabbatullāh is not an end goal, but rather an active process that begins from ritual obedience toward Divinely-oriented social interaction. This study concludes that Islamic education must shift its focus from normative obedience alone to developing pedagogical strategies based on Divine Love as the most important strategy in grounding transcendent spiritualism among learners.